Dr. Susan I. Moody's travels to Iran, 1909-1934 - Mahmoudi, Hoda, author.
1 online resource.
Keywords: "This volume examines the life of the remarkable woman, Susan Moody, and her travels to Iran in the early 20th century during seismic changes in the world. Dr. Susan I. Moody's Travels to Iran 1909-1934: Courageous Odyssey captures a fleeting moment of arresting change and shimmering possibility. Exploring the fading values of the 19th century and the emergent understandings of the 20th century, the author shows how one individual navigated such unique times. This book explores the Industrial Revolution, the rise of the women's movement, advances in medicine and healthcare, and the start of a new religion - The Baha'i Faith - of which Moody became a devoted member. Susan Moody was a pathbreaking artist and educator who became a physician later in life. She made the bold decision to leave the United States and travel to Iran in 1909 to serve women who effectively had no access to medical care. In examining Dr Susan Moody's story, this volume seeks to reflect on our own changing moment and the ever-present possibilities of improvement and advancement. By tracing her own courageous odyssey, we are invited to more deeply understand our own. This book will be of value to students and scholars alike interested in Women's and Gender history and Social and Cultural history"--